IMPLEMENTASI SISTEM PENJAMINAN MUTU PADA LEMBAGA PELATIHAN DAN PENDIDIKAN NONFORMAL - Intan Caroline; Holva Lovana Siregar (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to describe and analyze the implementation of a quality assurance system in training institutions and nonformal education as an effort to improve the quality of educational services and professional performance. The quality assurance system is viewed as a strategic mechanism that ensures all training processes, from planning and implementation to evaluation, are carried out in accordance with established standards. This research employed a qualitative approach using observation and interviews with managers of training institutions that implement an international quality management standard, namely ISO 21001:2018. The findings indicate that the implementation of a quality assurance system supported by leadership commitment, active involvement of all organizational members, and a sustainable quality culture contributes significantly to improving institutional effectiveness, human resource professionalism, and trainee satisfaction. Therefore, quality assurance systems function not only as control tools but also as instruments for continuous improvement in training institutions and nonformal education